2019
DOI: 10.3390/molecules24020265
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Allergic and Anti-Inflammatory Effects of Kuwanon G and Morusin on MC/9 Mast Cells and HaCaT Keratinocytes

Abstract: Atopic dermatitis (AD) is a prevalent chronic inflammatory skin disease. The use of immunomodulatory corticosteroids in AD treatment causes adverse side effects. Therefore, novel natural anti-inflammatory therapeutics are needed. The aim of the present study was to investigate the anti-allergic and anti-inflammatory activities of kuwanon G and morusin. To investigate the effect of kuwanon G and morusin on skin inflammation, enzyme-linked immunosorbent assays (ELISA) to quantitate secreted (RANTES/CCL5), thymus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 45 publications
1
33
0
Order By: Relevance
“…to 3.71 µM; kuwanon G: ≤ 3.13 µg/mL equiv. to 4.52 µM) are lower than the ones found to be cytotoxic in human normal cells (morusin: IC 50 = 9.48 µg/mL in human normal mammary epithelial cells (MCF-10A), IC 50 = 12.45 µg/mL in human normal liver cells (LO2), no alteration in viability of HaCaT keratinocytes and MC/9 mast cells at concentrations of up to 5 µM; kuwanon G: no alteration in viability of HaCaT keratinocytes and MC/9 mast cells at concentrations up to 20 and 10 µM, respectively) ( Gao et al, 2017 , Jin et al, 2019 , Li et al, 2015 ). Unfortunately, the isolation of pure phytochemicals from plant material is a complex, time-consuming, costly and low-yield process.…”
Section: Resultsmentioning
confidence: 99%
“…to 3.71 µM; kuwanon G: ≤ 3.13 µg/mL equiv. to 4.52 µM) are lower than the ones found to be cytotoxic in human normal cells (morusin: IC 50 = 9.48 µg/mL in human normal mammary epithelial cells (MCF-10A), IC 50 = 12.45 µg/mL in human normal liver cells (LO2), no alteration in viability of HaCaT keratinocytes and MC/9 mast cells at concentrations of up to 5 µM; kuwanon G: no alteration in viability of HaCaT keratinocytes and MC/9 mast cells at concentrations up to 20 and 10 µM, respectively) ( Gao et al, 2017 , Jin et al, 2019 , Li et al, 2015 ). Unfortunately, the isolation of pure phytochemicals from plant material is a complex, time-consuming, costly and low-yield process.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have confirmed the anti-inflammatory capacity of morusin in different in vivo and in vitro contexts—(1) Morusin treatment inhibits secretion of cytokines such as CCL5 and CCL17 in TNFα- and IFN-γ-stimulated keratinocytes and also inhibits the release of histamine and LTC 4 in A23187-stimulated MC/9 mast cells [ 24 ]. (2) Morusin treatment inhibits PMA-induced MUC5AC production in a human pulmonary mucoepidermoid cell line NCI-H292, showing prominent anti-inflammatory effects in vitro [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Although the mechanism underlying iNOS regulation by morusin has not been directly addressed yet, it may be recapitulated by the NF-κB pathway, a key intracellular pathway that governs pro-inflammatory signaling in multiple ways including reactive oxygen species (ROS) production, cytokine production and immune cell activation [ 32 , 33 ]. Furthermore, morusin suppressed STAT1-mediated cytokine secretion in TNF-α- and IFN-γ-stimulated keratinocytes [ 24 ]. Indeed, many studies have already emphasized that the versatile effects of morusin may be associated with downregulation of the NF-κB pathway and its crosstalk with STAT1, STAT3 and Wnt/β-catenin signaling [ 24 , 25 , 26 , 29 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…In fact, Morusin was believed to reduce the inflammatory reaction in several diseases. 17,36,37 We, therefore, explored whether it possessed anti-inflammatory properties in osteoarthritis. Our data demonstrate that Morusin significantly inhibits the IL-1β-induced inflammatory reaction in chondrocytes; potentially via suppression of the NF-κB signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…15 This compound has been found to engage in a myriad of biological functions, including anti-inflammatory, antioxidative and antitumor activities. [16][17][18] For instance, Morusin was reported to attenuate LPS-induced proinflammatory responses in RAW264.7 cells. 19 Additionally, an in vivo study revealed that Morusin ameliorates 2, 4, 6-trinitrobenzene sulfonic acid sodium salt (TNBS)induced colitis in rats.…”
Section: Introductionmentioning
confidence: 99%